Retrospective cohort study of 925 OAGB procedures. The UK MGB/OAGB collaborative group. (September 2019) - Hussain, A.; Van den Bossche, M.; Kerrigan, D.D.; Alhamdani, A.; Parmar, C.; Javed, S.; Harper, C.; Darrien, J.; Singhal, R.; Yeluri, S.; Vasas, P.; Balchandra, S.; et al.
Abstract: Background: Mini-One Anastomosis Gastric Bypass is a new operation that provides comparable outcomes to the common bariatric procedures. Revisional surgery is still needed after a number of MGB-OAGB procedures. The aim of this study is to report the causes and management of these revisions. Methods: From 2010 to 2018, 925 MGB-OAGB operations were performed at 7 bariatric units across the United Kingdom and included in this retrospective cohort study. The data was retrospectively collected and analysed. The primary end point was the identification of the causes and management of revisions. Follow up ranged from 6 months to 3 years. Results: Twenty-two patients [2.3%] required revisional surgery after MGB-OAGB. Five patients [0.5%] developed severe diarrhoea managed by shortening the bilio-pancreatic limb to 150 cm. Four patients [0.4%] developed afferent loop syndrome and bile reflux was reported in another 3 [0.3%] cases; all were managed by either conversion to Roux en Y Gastric Bypass or a Braun anastomosis. Postoperative bleeding was controlled laparoscopically in 3 patients [0.3%]. Liver decompensation that was reported in 2 patients [0.2%] was treated by shortening the BPL in one patient and a reversal to normal anatomy in another. The liver failure resolved in both patients. Other indications for revision included two gastro-jejunal stenosis [0.2%], one perforated ulcer [0.1%], one patient [0.1%] with excessive weight loss and one case [0.1%] of protein malnutrition. None of the 22 patients undergoing revisional surgery after MGB-OAGB died. Lost to follow up rate was 0.2%. Conclusion: Complications requiring revisional surgery after MGB-OAGB are uncommon [2.3%] and the majority can be managed by bilio-pancreatic limb shortening, the addition of a Braun side-to-side anastomosis or conversion to RYGB. Bilio-pancreatic limb length of 200 cm or more resulted in serious complications of liver failure, protein malnutrition, excessive weight loss and diarrhoea. Highlights: The most important findings of this study are the outstanding safety and low revision rate. Complications are reported in 2.3% and managed by shortening the BPL, Braun anastomosis or RYGB.3.BPL of 200 cm is associated with most serious complications.